2019
DOI: 10.1093/ptep/ptz058
|View full text |Cite
|
Sign up to set email alerts
|

Holographic subregion complexity of a (1+1)-dimensional $p$-wave superconductor

Abstract: We analyze the holographic subregion complexity in a 3d black hole with the vector hair. This 3d black hole is dual to a 1 + 1 dimensional p-wave superconductor. We probe the black hole by changing the size of the interval and by fixing q or T . We show that the universal part is finite across the superconductor phase transition and has competitive behaviors different from the finite part of entanglement entropy. The behavior of the subregion complexity depends on the gravitational coupling constant divided by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 100 publications
(149 reference statements)
2
7
0
Order By: Relevance
“…Our results are in agreement with that reported in [44] and in [45] where the authors have studied 1 + 1-dimensionsal s-wave and p-wave holographic superconductor respectively: the complexity remains finite during the phase transition 3 and the subregion complexity plot leads to the same transition temperature as observed from the entropy plot. Ref.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are in agreement with that reported in [44] and in [45] where the authors have studied 1 + 1-dimensionsal s-wave and p-wave holographic superconductor respectively: the complexity remains finite during the phase transition 3 and the subregion complexity plot leads to the same transition temperature as observed from the entropy plot. Ref.…”
Section: Discussionsupporting
confidence: 92%
“…Ref. [45] has also observed multivaluedness and discontinuous but finite jump in the complexity during the first order phase transition.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Initially, the holographic entanglement entropy and the holographic complexity are obtained for a strip in our model [21]- [33], [35,36]. In order to use the Poincare coordinates we choose a time slice in the metric (13) and replace the coordinate r by 1 ξ .…”
Section: Topological Invariants and The Critical Pointsmentioning
confidence: 99%
“…Also, it has been suggested that holographic subregion complexity (RT volume) can be used as a useful tool for probing superconductor phase transitions. Therefore, both holographic entanglement entropy and holographic subregion complexity are useful quantities to identify superconductor phase transitions [35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%